2023
DOI: 10.1002/2688-8319.12223
|View full text |Cite
|
Sign up to set email alerts
|

Where should they come from? Where should they go? Several measures of seed source locality fail to predict plant establishment in early prairie restorations

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…The United Nations' challenge to restore millions of hectares of land during 2021-2030 (the 'decade on restoration') will require considerable effort and guidance as to how best to implement research and practical protocols to maximize the recovery of biodiversity across restored ecosystems worldwide. Co-designing research will be pivotal in achieving these targets, and Pizza et al (2023) demonstrated this by creating a collaboration between academic scientists, a native seed producer and land stewards to better understand factors related to maximizing plant habitat restorations. Their work demonstrates that the restoration of tallgrass prairies is not amplified when using seed sources considered 'local'; rather, greater seeding rates and increased management of the restoration site after seeding are the elements needed to increase the likelihood that native species will successfully establish.…”
Section: Co -De S I G Ned Projec Ts For In Cre a S Ing B I Od Iver S ...mentioning
confidence: 99%
“…The United Nations' challenge to restore millions of hectares of land during 2021-2030 (the 'decade on restoration') will require considerable effort and guidance as to how best to implement research and practical protocols to maximize the recovery of biodiversity across restored ecosystems worldwide. Co-designing research will be pivotal in achieving these targets, and Pizza et al (2023) demonstrated this by creating a collaboration between academic scientists, a native seed producer and land stewards to better understand factors related to maximizing plant habitat restorations. Their work demonstrates that the restoration of tallgrass prairies is not amplified when using seed sources considered 'local'; rather, greater seeding rates and increased management of the restoration site after seeding are the elements needed to increase the likelihood that native species will successfully establish.…”
Section: Co -De S I G Ned Projec Ts For In Cre a S Ing B I Od Iver S ...mentioning
confidence: 99%